Assessment of mechanical dyssynchrony can improve the prognostic value of guideline-based patient selection for cardiac resynchronization therapy. (22nd February 2018) - Beela, Ahmed S; Ünlü, Serkan; Duchenne, Jürgen; Ciarka, Agnieszka; Daraban, Ana Maria; Kotrc, Martin; Aarones, Marit; Szulik, Mariola; Winter, Stefan; Penicka, Martin; Neskovic, Aleksandar N; Kukulski, Tomasz; et al.
Abstract: Aim: To determine if incorporation of assessment of mechanical dyssynchrony could improve the prognostic value of patient selection based on current guidelines. Methods and results: Echocardiography was performed in 1060 patients before and 12 ± 6 months after cardiac resynchronization therapy (CRT) implantation. Mechanical dyssynchrony, defined as the presence of apical rocking or septal flash was visually assessed at the baseline examination. Response was defined as ≥15% reduction in left ventricular end-systolic volume at follow-up. Patients were followed for a median of 59 months (interquartile range 37–86 months) for the occurrence of death of any cause. Applying the latest European guidelines retrospectively, 63.4% of the patients had been implanted with a Class I recommendation, 18.2% with Class IIa, 9.4% with Class IIb, and in 9% no clear therapy recommendation was present. Response rates were 65% in Class I, 50% in IIa, 38% in IIb patients, and 40% in patients without a clear guideline-based recommendation. Assessment of mechanical dyssynchrony improved response rates to 77% in Class I, 75% in IIa, 62% in IIb, and 69% in patients without a guideline-based recommendation. Non-significant difference in survival among guideline recommendation classes was found (Log-rank P = 0.2). Presence of mechanical dyssynchrony predicted long-term outcome better than guideline Classes I, IIa, IIb (Log-rank P < 0.0001, 0.006, 0.004, respectively) and in patients with no guideline recommendation ( P = 0.02). Comparable results were observed using the latest American Guidelines. Conclusion: Our data suggest that current guideline criteria for CRT candidate selection could be improved by incorporating assessment of mechanical asynchrony.